KONSTRUKSI WACANA PENUNDAAN PEMILU 2024 PADA PROGRAM DUA SISI TVONE (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The purpose of this study was to analyze the news framing scheme for the issue of postponing the 2024 Election on TVOne's "Dua Sisi" program, the More Gaduh episode of President's Term Extension. This study uses a qualitative approach with the method of media framing analysis, namely the Robert N Etman framing analysis model. The data collection technique was carried out by analyzing documents related to the discourse on the postponement of the 2024 Election and dividing it into four elements, namely (problem) defining the problem, (diagnosing causes) estimating the source of the problem, (making moral judgment) moral decision, (treatment recommendation) emphasizing resolution. The results of this study indicate that TVOne's “Dua Sisi” program tends to defend the president. Defining the problem in the discourse of postponing the 2024 election is against the constitution, the estimated source of the problem of postponing the election heats up after it was raised by three political parties supporting Jokowi, moral decisions should be subject to and obey the constitution, emphasizing the solution, namely that everyone has the right to voice their opinion as a democratic country. The construction of news about the postponement of the 2024 election can be seen from the topics of discussion, the arrangement of questions or narratives, the selection of sources, and the display of visual images showing a tendency to construct news. The implication of this research is that the media is able to lead public opinion from news that is constructed to be conveyed to the public. Newsreaders should not receive information from just one source.